Current Perspectives of Prenatal Sonographic Diagnosis and Clinical Management Challenges of Complex Umbilical Cord Entanglement - Sherer DM; Roach C; Soyemi S; Dalloul M (Dove Medical Press, 2021)
David M Sherer, Crystal Roach, Sarin Soyemi, Mudar Dalloul The Division of Maternal-Fetal Medicine, The Department of Obstetrics and Gynecology, State University of New York (SUNY), Downstate Health Sciences University, Brooklyn, NY, USACorrespondence: David M ShererDivision of Maternal-Fetal Medicine, Department of Obstetrics and Gynecology, State University of New York (SUNY), Downstate Health Sciences University, 450 Clarkson Avenue, Box 24, Brooklyn, NY, 11203, USATel +1 718 270-2081Fax +1 718 270-4122Email davidmsherer@gmail.comAbstract: Diagnosis of potential umbilical cord compromise, namely, true knots of the umbilical cord and nuchal cords has been enabled with increasing accuracy with current enhanced prenatal sonography. Often an incidental finding at delivery, the incidence of true knots of the umbilical cord has been estimated at between 0.04% and 3% of deliveries. This condition has been reported to account for a 4 to 10-fold increase of stillbirth and perinatal morbidity of 11% of cases. Nuchal cords, commonly observed at the delivery of uncompromised, non-hypoxic non-acidotic newborns occur more frequently with single nuchal cords noted in between 20% and 35% of all deliveries at term. Multiple nuchal cords are considerably less frequent, with decreasing frequencies inverse to the number of nuchal cord loops. While clearly single (and likely double) nuchal cords are almost uniformly associated with favorable neonatal outcomes, emerging data suggest that cases of ≥ 3 loops of nuchal cords are more likely to be associated with an increased risk of adverse perinatal outcome (either stillbirth or compromised neonatal condition at delivery). We define cases of a true knot of the umbilical cord, cases of ≥ 3 loops of nuchal cords, any combination of a true knot and nuchal cord, or any umbilical cord entanglement (nuchal or true knot) in the presence of a single umbilical artery, in singleton gestations as complex umbilical cord entanglement. Two concurrent developments, the increase in accuracy of prenatal sonographic diagnosis of complex umbilical cord entanglement and recent data confirming fatal compromise of the umbilical circulation in approximately 20% of cases of stillbirth, suggest that establishing governing body guidelines for reporting of potential umbilical cord compromise, and recommendation of consideration for early-term delivery of select cases, may be warranted. This commentary will address current perspectives of prenatal diagnosis and clinical management challenges of complex umbilical cord entanglement.Keywords: prenatal ultrasound, complex umbilical cord entanglement, true knot of the umbilical cord, nuchal cord, clinical management